Progressivism and training of intellectuals in Peru- The work of Giesecke, rector of the University of Cusco - Giesecke, Mercedes (2017)
The education of intellectuals in Peru between 1910 and 1923, helped develop a very close relationship between intelligence and ethics through persuasion for the nonviolent and highly rational performative action and Panamerican community. Process marked by the presence in a West mentality, oriented enthusiasm to achieve better standards of democratic and modern life through the expansion of the progress, between 1870 and 1920. Reflecting this ultimate in mass media communication, railroads, newspapers, political participation, the expansion of work and the improvement of the quality of life. The Peruvian intellectuals and politicians at the beginning of the twentieth century reinforced this situation, guided by the changes in American society and influenced so, they translated this for the Peruvian case. Which is reflected in the action of the rector of Cusco: Dr. Giesecke.